Upaya Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Teams Games Tournament (TGT) pada Materi Luas di Kelas IV SD Negeri 1 Banjarsari Kulon - Yulianti Estiana Rahmawati; Sri Muryaningsih (Journal on Education, 2024)
Classroom action research was carried out because there were problems that occurred at SD N 1 Banjarsari Kulon. These problems include the low learning outcomes of class IV students and the use of inappropriate learning models. The aim of this research is to improve student learning outcomes through the Teams games tournament learning model. The technique used to obtain data quantitatively is through learning outcomes in the form of evaluation scores given at the end of the lesson. Apart from that, data collection was also carried out by means of observation and interviews. Observations were carried out during the learning process in the form of observing student and teacher activities, while interviews were conducted with the teacher and 3 class IV students. The results of this study showed an increase of 70% in cycle I and 87% in cycle II. This Tgt learning model has a positive influence on student learning outcomes seen from the assessment results obtained in cycles I and II. The number of students who got good grades also increased, from 21 students who completed the first cycle to 26 students in the second cycle. Thus it can be concluded that the TGT learning model can improve student learning outcomes in the cognitive, affective, and psychomotor aspects of class IV SD N 1 Banjarsari Kulon.